Lymphoproliferative response and T lymphocyte subsets in a medium-term multi-organ bioassay for carcinogenesis in Wistar rats - Spinardi-Barbisan, ALT; Kaneno, Ramon [UNESP]; Rodrigues, MAM; Salvadori, Daisy Maria Favero [UNESP]; Moreira, ELT; Barbisan, Luis Fernando [UNESP]; de Camargo, JLV (Elsevier B.V., 2000)
The lymphoproliferative response and T lymphocyte subsets were evaluated at different stages of carcinogenesis in male Wistar, rats sequentially initiated with N-diethylnitrosamine (DEN), N-butyl-N-4(hydroxybutyl)nitrosamine (BBN), N-methyl-N-nitrosourea (MNU), dihydroxy-di-N-propylnitrosamine (DHPN) and N,N'-dimethylhydrazine (DMH) (DMBDD initiation). One group was evaluated at the 4th week and other initiated group at the 30th week. Two initiated groups were also exposed through diet to 7-acetylaminofluorene (2-AAF) or phenobarbital (PB), from the 6th until the 30th week. Two groups received only 2-AAF or PB until the 30th week. Five groups were studied to evaluate the effects of each initiator. The lymphoproliferative response was induced in vitro by concanavalin A and the percentage of T lymphocyte subsets was determined by flow cytometry, All groups submitted to initiation only, initiation plus promotion, or promotion only, developed significantly more preneoplastic: lesions than the untreated control group. The main target organs for tumor development were the liver, colon, urinary bladder, kidneys and Zymbal glands, mainly in the group treated with DMBDD + 2-AAF, There were no alterations of the lymphoproliferative response and of the T lymphocyte subsets percentage in the DMBDD-treated group at the 4th and 30th weeks. At the 30th week, the T lymphocyte subsets percentage was also not affected in the initiated groups after treatments with 2-AAF or PB. The lymphoproliferative response, however, was decreased in the DMBDD + 2-AAF group and in the groups treated only with 2-AAF or PB, the present results indicate that the initiating chemicals used in the DMBDD initiation protocol do not exert any influence on the immune system. The alteration of lymphoproliferative response induced at the advanced stage of carcinogenesis without alteration of T lymphocyte subsets may indicate that the influence of 2-AAF and PB on the immune system is functional and not toxic. (C) 2000 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: lymphoproliferative response; lymphocyte subsets; flow cytometry; cancer; multi-organ carcinogenesis; chemical carcinogens